Dry powder microneedle-enabled transdermal anti-inflammatory therapy for obesity, diabetes, hyperlipidemia, and fatty liver - Zan, Ping (2024)
Obese white adipose tissue (WAT) is characterized by hypoxia, oxidative stress, and inflammation, which are the key drivers of various deleterious diseases. Herein, we demonstrate a new strategy to directly induce ameliorative remodeling of obese subcutaneous WAT (sWAT). Manganese dioxide nanoparticle, which can directly react with hydrogen peroxide and produce oxygen, and has nanocatalytic abilities mimicking superoxide dismutase and catalase, is transdermally delivered together with a natural antioxidant resveratrol, leading to reduction of oxidative stress, hypoxia, and consequently suppression of inflammation in obese sWAT. The localized treatment not only leads to remodeling of the targeted sWAT and large reduction of its mass, but also improves whole-body metabolism as evidenced by total relief of diabetes, and significant decrease of visceral fat, liver fat, hyperlipidemia, and systemic inflammation. For self-administrable and minimally-invasive transdermal delivery, a new type of microneedle is designed, which is made purely by dry powders of the therapeutics and offers a loading capacity 2 orders higher than the conventional microneedles. Moreover, the intricate signaling pathways underlying this transdermal anti-inflammatory therapy are revealed.